2021
DOI: 10.3390/f12050554
|View full text |Cite
|
Sign up to set email alerts
|

Short-Rotation Willows as a Wastewater Treatment Plant: Biomass Production and the Fate of Macronutrients and Metals

Abstract: Evapotranspirative willow systems (EWS) are zero-discharge wastewater treatment plants that produce woody biomass and have no discharge to surface or groundwater bodies. The influence of wastewater on the growth of three clones of Salix alba (‘V 093’, ‘V 051’ and ‘V 160’) and the distribution of macronutrients and metals in a pilot EWS receiving primary treated municipal wastewater was studied under a sub-Mediterranean climate. The influent wastewater, shoot number, stem height, and biomass production at coppi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…This result indicates that the application of chemical fertilizers in soil not only increases the content of ionic P in maize rhizosphere soil, but also transforms the chemically mobilized P (such as O-P, Ca-P) into the ionic state due to the decrease of soil pH. In this process, although mobilized P is conducive to plant absorption (Schillaci et al 2021;Istenič and Božič 2021;Pedro et al 2021;Suresh et al 2021), and can also increase the risk of soil phosphorus loss with surface runoff (Boero 1977;Li et al 2013;Temporetti et al 2019). Some studies have shown that the organic acids exuded by plant roots reduce the pH of the rhizosphere soil and promotes the release of ionic P. And with the decrease of H + and organic acid in the soil, the insoluble phosphorus compounds (such as calcium phosphate compounds, hydroxy aluminum phosphate (iron) compounds) in the soil are hydrolyzed and dissociated into H2PO4 -, HPO4 2and other ionic states ( (Hayes et al 2000;Boafo et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…This result indicates that the application of chemical fertilizers in soil not only increases the content of ionic P in maize rhizosphere soil, but also transforms the chemically mobilized P (such as O-P, Ca-P) into the ionic state due to the decrease of soil pH. In this process, although mobilized P is conducive to plant absorption (Schillaci et al 2021;Istenič and Božič 2021;Pedro et al 2021;Suresh et al 2021), and can also increase the risk of soil phosphorus loss with surface runoff (Boero 1977;Li et al 2013;Temporetti et al 2019). Some studies have shown that the organic acids exuded by plant roots reduce the pH of the rhizosphere soil and promotes the release of ionic P. And with the decrease of H + and organic acid in the soil, the insoluble phosphorus compounds (such as calcium phosphate compounds, hydroxy aluminum phosphate (iron) compounds) in the soil are hydrolyzed and dissociated into H2PO4 -, HPO4 2and other ionic states ( (Hayes et al 2000;Boafo et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted however that these theoretical assumptions usually result in very high potential areas for SRC. SRC can be used as a wastewater treatment plant for pre-treated domestic wastewater (Istenič et al, 2021).…”
Section: Availability Of Land For Src In Flandersmentioning
confidence: 99%
“…The biomass production of Phragmites australis, the most common plant used in TWs, is 19 ± 13 t ha −1 y −1 when used for the secondary treatment of domestic wastewater [34]. A special type of TW, so-called evapotranspirative systems, wherein short-rotation willows are planted in the treatment beds, can produce more biomass as reeds, e.g., 22-26 t wood chips ha −1 y −1 [35,36].…”
Section: In-and Outputsmentioning
confidence: 99%
“…TW are addressing numerous urban challenges: via wastewater, they provide reclaimed water for irrigation or fertigation, thus contributing to the restoration and maintenance of the urban water cycle [47]. Additionally, the produced plant biomass can be composted, contributing to nutrient recovery and reuse, or used for energy production [36,47]. TW plant biomass can be used as construction material in ecologically oriented construction as raw material for rooves, but different materials can also be produced from it, such as composite panels or insulation material [48][49][50].…”
Section: Contribution Of This Nbs Unit To the Mitigation Of Urban Circularity Challengesmentioning
confidence: 99%